Development of Augmented Reality-Based Learning Media on Virus Material for High School Students - Mahmudah, Yulia Nasibatul; Gazali, Zulkarnain; Nurmiati, Nurmiati (Lombok Institute, 2023)
This research aims to develop and describe the feasibility of Augmented Reality-based learning media as a medium for virus material for 10th grade science students. This research is a development study that adopts the 4D Thiagarajan model which includes Define, Design, Development, and Disseminate. The subjects of this study were 42 10th grade science students. The object of this study is biology learning media based on Augmented Reality which was validated by 3 validators. The results of material expert validation showed that the learning media scored 84% and was categorized as Very Feasible, while the media assessment by media experts scored 78% and was categorized as Feasible. In addition, the study field teacher’s assessment of the learning media scored 84% and was categorized as Very Feasible, while the student questionnaire results scored 95% with the category of Very Feasible. The results of this study indicate that Augmented Reality-based learning media is Very Feasible to be used to support the learning process.